Bandwidth Enhancement of Metamaterial Loaded Microstrip Antenna using Double Layered Substrate - V. Srinivasa Rao; K.V.V.S. Reddy; A.M. Prasad (Institute of Advanced Engineering and Science, 2017)
Communication has become a key aspect of our daily life, becoming increasingly portable and mobile. This would need the use of micro strip antennas. The rapid growth has led to the need of antennas with smaller size, increased bandwidth and high gain. In this paper, a new version of micro strip patch antenna is designed by adopting double layered substrate concept and adding a layer of metamaterial structure to a square micro strip antenna. The antenna properties gain, return loss and bandwidth are studied to achieve better performance. The designed patch antenna has an improved bandwidth of 60% at a resonant frequency of 2.47 GHz. This antenna is designed and simulated by using HFSS software.